Cross-cultural adaptation and psychometric validation of The Continuous Traumatic Stress Response Scale: Ukrainian version - Zasiekina, Larysa; Goral, Aviva; Fedotova, Tetiana; Akimova, Anastasiya; Martyniuk, Anastasiia (Lesya Ukrainka Eastern European National University, 2024)
Adapting and validating diagnostic tools aimed to evaluate the post-traumatic effects of war in low-income countries is essential for assessing needs and planning support programs. This paper will describe the process of cross-cultural adaptation and psychometric validation of The Continuous Traumatic Stress Response (CTSR) Scale for war-affected Ukraine. The study includes Phase 1, Translation and cross-cultural adaptation of the Scale, and Phase 2, Psychometric validation of the Scale. Cross-cultural adaptation goes through four stages: forward translation, expert panel review and back translation (n=3), pretesting and cognitive interviewing mental health professionals (n=8), and final version. Psychometric validation includes exploratory (n=200) and confirmatory (n=419) factor analyses, internal consistency, construct validity and test-retest reliability. Findings from the current research indicate that the components identified through factor analyses differed from those in the original questionnaire. While all original items in the questionnaire were retained, they merged into two new factors: “Exhaustion and Rage” and “Fear and Betrayal”. The results show that the overall Cronbach’s Alpha is .858, indicating a high level of internal consistency. Significant correlations exist between the total CTSR Scale score, the subscale scores, PTSD (PCL-5), moral injury (MISS-C-SF), depression (PHQ-9), and anxiety (GAD-7) symptoms, indicating construct validity. The findings demonstrate the test-retest reliability of the CTSR Scale and have practical implications for how it could be implemented in trauma-informed care.
Keywords: continuous traumatic stress; moral injury; secondary traumatic stress; cross-cultural adaptation; translation; validation